Resource efficiency impact on marble waste recycling towards sustainable green construction materials - Thakur, Anil Kumar; Pappu, Asokan; Thakur, Vijay Kumar (Elsevier, 2018)
India is one of the biggest marble producing country in the world (∼10%). State of Rajasthan has nearly 85% of marble production capacity. Recently, the massive quantity of marble waste fine particulates generated in marble industry has become a major environmental hazard issue. Major minerals present in marble waste are calcite (CaCO3) and dolomite (CaMg (CO3)2). The particle sizes of marble waste particulates has been found to be 200 μm (D90). The chemical composition of marble wastes reveals oxides of calcium (CaO), silica (SiO2), alumina (Al2O3) and alkaline oxides (Na2O, K2O). Apart from that, iron oxide, mica, fluorine, chlorite and organic matter have also been noticed. Marble waste has been explored for possible utilization in industries, thereby it helps in preventing the environmental problems such as dumping and pollution. This article addresses the efficiency of marble wastes for materials development, leading to create some sustainable green composite materials for construction applications.